A different form of injury prevention: Successful screening and referral for human immunodeficiency virus and hepatitis C virus in a trauma population. Issue 5 (November 2018) - Privette, Alicia R.; White, Benjamin; Ferguson, Pamela L.; Norcross, E. Douglas; Richey, Lauren E.
Abstract : BACKGROUND: In the United States, millions of patients are living with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) (0.44% and 1.5%) and many are currently undiagnosed. Because highly effective treatments are now available, early identification of these patients is extremely important to achieve improved clinical outcomes. Prior data and trauma-associated risk factors suggest a higher prevalence of both diseases in the trauma population. We hypothesized that a screening program could be successfully initiated among trauma activation patients and that a referral and linkage-to-care program could be developed. METHODS: Hepatitis C virus and HIV screening tests were added to standard trauma activation laboratory orders at an academic Level I Trauma Center. Confirmatory viral load was sent when indicated. Patients with positive results were educated about their disease and referred to disease-specific follow-up. Data were collected prospectively from January 1, 2016, until June 30, 2017. Total and new diagnosis, referral rates, and linkage-to-care rates were analyzed. RESULTS: One thousand eight hundred ninety-eight patients arrived as trauma activations. One thousand two hundred seventeen (64.1%) patients were screened (Level A, 75.6%; Level B, 60.2%). Seven percent of the screened patients were initially positive, and 5.5% were confirmed positive. Rates of both HIV (1.1%) and HCV (4.4%) were almost triple the national average. Overall, 3.3% screened positive for a new diagnosis. For HCV, the rate of new diagnosis was twice the national average (3%). Over 85% of all cases were referred for follow-up, and the combined linkage-to-care rate was 43.3%. CONCLUSION: The majority of patients were screened and referred for follow-up, indicating successful implementation of our trauma screening program. Routine screening of trauma patients should be considered to increase diagnosis rate, increase linkage-to-care rates, and decrease disease transmission. These screening efforts would help bridge the health care gap that exists in the trauma population due to lower insurance rates and limited access to primary care. LEVEL OF EVIDENCE: Therapeutic/Care management, level III.